2009
DOI: 10.1210/en.2008-1662
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of α5-Integrin by E-Cadherin Loss in Hypoxia and Its Key Role in the Migration of Extravillous Trophoblast Cells during Early Implantation

Abstract: During early pregnancy, cytotrophoblast cells differentiate into extravillous trophoblast (EVT) cells and invade the uterine spiral arteries. This physiological process is essential for the development of maternal-fetal circulation. Because EVT cells are exposed to a low-oxygen environment during this process, we investigated the role of hypoxia in the mechanism that regulates the invasive behavior of EVT cells. Real-time PCR and immunofluorescent analysis were performed to investigate how hypoxia influences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…They suggested that during early placentation, low-oxygen tension up-regulates SNAIL in EVTs, which in turn down-regulates E-cadherin expression and subsequently increases adhesion and invasion. 53 This preliminary evidence of a role for SNAIL in placental cells is consistent with a potentially important role in early placental development and EMT, which warrants further investigation. SLUG is another member of the SNAIL family of transcriptional repressors.…”
Section: Transcriptional Regulation Of Emtsupporting
confidence: 63%
See 1 more Smart Citation
“…They suggested that during early placentation, low-oxygen tension up-regulates SNAIL in EVTs, which in turn down-regulates E-cadherin expression and subsequently increases adhesion and invasion. 53 This preliminary evidence of a role for SNAIL in placental cells is consistent with a potentially important role in early placental development and EMT, which warrants further investigation. SLUG is another member of the SNAIL family of transcriptional repressors.…”
Section: Transcriptional Regulation Of Emtsupporting
confidence: 63%
“…The inverse relationship between SNAIL and E-cadherin observed in epithelial and cancer cells also exists in a number of trophoblast cell lines. 52,53 Arimoto-Ishida et al, 53 investigated the role of SNAIL in trophoblast invasion and showed that down-regulating SNAIL siRNA resulted in decreased invasiveness of trophoblast-derived cell lines. They suggested that during early placentation, low-oxygen tension up-regulates SNAIL in EVTs, which in turn down-regulates E-cadherin expression and subsequently increases adhesion and invasion.…”
Section: Transcriptional Regulation Of Emtmentioning
confidence: 99%
“…Activity of this enhancer is associated with enrichment of H3 Lys (4) dimethylation and H3 acetylation of both the enhancer and promoter. Although hypoxia has been implicated in upregulation of Snail (19)(20)(21), no functional hypoxia-responsive element has been identified in the snail promoter.…”
Section: D a Bmentioning
confidence: 99%
“…GSK-3 is an endogenous inhibitor of Snail transcription (17) and GSK-3b mediated phosphorylation of Snail has been shown to facilitate its proteasomal degradation (18). Low oxygen induces Snail transcription (19)(20)(21)(22) and both the canonical HIF (22,23) and Notch (24,25) pathways have been implicated in hypoxia-induced EMT. However, Snail is yet to be identified as a direct HIF target gene.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, 18 ␣ and 8 ␤ subunits have been characterized, which combine to generate 24 unique integrin heterodimers (26). Multiple integrin subunits are up-regulated under hypoxic conditions in a range of cell types (5,27,28). Among these, integrin ␣3␤1 is an enigmatic member of the integrin family, and the regulation of its function also marks it as distinct from that of other integrins (29).…”
mentioning
confidence: 99%